2018
DOI: 10.4028/www.scientific.net/msf.941.426
|View full text |Cite
|
Sign up to set email alerts
|

Porosity Developments within 9Cr-1Mo Steel Exposed to CO<sub>2</sub>

Abstract: When 9Cr-1Mo steel is exposed to CO2-rich advance gas-cooled reactor (AGR) gases it forms a duplex oxide which consists of an outer Fe rich layer and an inner Cr rich spinel which provides oxidation resistance allowing the steel to resist the corrosive atmosphere of the plant. The oxide scale develops, growing both into the substrate and outwards from the initial metal/air interface. The spinel develops porosity through the coalescence of Fe vacancies which over time alters the properties of the oxide and pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…These samples, in comparison to samples shown in Figures 7 and 8, have been exposed for a shorter duration. These were chosen as it has been previously [41] been observed that samples which have been exposed and suffered breakaway show very little internal oxidation zone and very thick breakaway oxide which has a very different structure to pre-breakaway oxide.…”
Section: Internal Oxidation Zone (Ioz)mentioning
confidence: 99%
“…These samples, in comparison to samples shown in Figures 7 and 8, have been exposed for a shorter duration. These were chosen as it has been previously [41] been observed that samples which have been exposed and suffered breakaway show very little internal oxidation zone and very thick breakaway oxide which has a very different structure to pre-breakaway oxide.…”
Section: Internal Oxidation Zone (Ioz)mentioning
confidence: 99%
“…This is in contrast to previous work where it was thought that the only way to accurately analyse the porosity though the oxide was by using a FIB [32]. The 2D porosity area fraction has previously been investigated by the authors where various samples are compared, and this showed the development of porosity with exposure, with the area fraction and oxide thickness increasing with exposure time and with the characteristic banding of the Cr-rich spinel clearly visible [28].…”
Section: Porosity Discussionmentioning
confidence: 71%
“…Porosity changes within the oxide of 9Cr-1Mo steel exposed to CO 2 have been previously investigated using SEM imaging techniques [28], but SEM micrographs only give a 2D snapshot into the oxidation processes and porosity development taking place within the oxide scale. In comparison with traditional SEM imaging, focused ion beam microscopy allows for the removal of material, either as a large section or very thin layers (\ 100 nm).…”
Section: Introductionmentioning
confidence: 99%